Food insecurity among households with children during the early months of the COVID-19 pandemic - Bailey Houghtaling; Lindsey Haynes-Maslow; Lauri Andress; Annie Hardison-Moody; Michelle Grocke-Dewey; Denise Holston; Megan Patton-López; Nila Pradhananga; T. Prewitt; Justin Shanks; Eliza Webber; Carmen Byker Shanks (Journal of Agriculture, Food Systems, and Community Development, 2023)
Understanding impacts of the COVID-19 pandemic among households with children is necessary to design appropriate public health responses that protect food and nutrition security. The objective of this research was to understand predictors of food insecurity during the COVID-19 pandemic among households with at least one child (<18 years), including whether foods reported as out-of-stock were associated with the likelihood of food insecurity. An online survey using validated measures and open-ended questions was distributed to a convenience sample in five states—Louisiana, Montana, North Carolina, Oregon, and West Virginia—during the early months of the COVID-19 pandemic (April through September of 2020). Predictors of food insecurity (race/ethnicity, age, marital status, education, federal nutrition assistance program participation, number of adults and children in the household, rurality, and missing foods when shopping) among households with children during the COVID-19 pandemic were modeled using logistic regression (p < 0.05, a priori). To further illuminate household experiences during this time, two researchers independently coded open-ended survey question data using inductive and deductive approaches to construct themes. Households with children had increased odds of experiencing food insecurity during the COVID-19 pandemic if they had the following characteristics: Hispanic ethnicity; age between 25 and 44 years; additional adult household members; economic hardship; SNAP/WIC participation; being widowed, divorced, or separated; and reporting foods not available when shopping. Participants described mainly negative changes to dietary patterns and practices as a result of the COVID-19 pandemic. They also described food security challenges and ideas for improving food security. Consistent with other data collected and analyzed during the height of the COVID-19 pandemic, this study contributes findings that emphasize the need for enhanced public health responses and emergency preparedness measures that protect food and nutrition security. Because of the increased short- and long-term consequences including exposure to adverse circumstances, impaired learning, risks to mental health, and poor health outcomes, ensuring an adequate food supply is especially important for households with children.